2014
DOI: 10.1053/j.gastro.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Pancreas Epithelial Cells in Patients With Pancreatic Cystic Lesions

Abstract: Hematogenous dissemination is thought to be a late event in cancer progression. We showed recently that pancreas cells can be detected in the bloodstream before tumor formation, in a genetic model of pancreatic ductal adenocarcinoma (PDAC). To confirm these findings in humans, we used microfluidic geometrically enhanced immunocapture to detect circulating pancreas epithelial cells (CECs) in patient blood samples. We captured >3 CECs/ml in 7 of 21 (33%) of patients with cystic lesions and no clinical diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
133
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(152 citation statements)
references
References 9 publications
10
133
0
1
Order By: Relevance
“…The pancreas tumor microenvironment has been studied previously, but new tools [genetically engineered mouse models (GEMs) that faithfully recapitulate the salient features of human PDAC] now allow for a careful dissection of the stroma. Using these models, we showed that generalized inflammation is required for the development of precancerous pancreatic intraepithelial neoplasias (1) and that Hedgehog-dependent stromal elements, including activated myofibroblasts, serve to constrain tumor growth and spread (2). Other cellular components of the pancreatic inflammatory stroma have not been examined, and it is possible they also contribute to the complex balance of inputs, supportive and inhibitory, which underlie tumorigenesis and progression.…”
mentioning
confidence: 99%
“…The pancreas tumor microenvironment has been studied previously, but new tools [genetically engineered mouse models (GEMs) that faithfully recapitulate the salient features of human PDAC] now allow for a careful dissection of the stroma. Using these models, we showed that generalized inflammation is required for the development of precancerous pancreatic intraepithelial neoplasias (1) and that Hedgehog-dependent stromal elements, including activated myofibroblasts, serve to constrain tumor growth and spread (2). Other cellular components of the pancreatic inflammatory stroma have not been examined, and it is possible they also contribute to the complex balance of inputs, supportive and inhibitory, which underlie tumorigenesis and progression.…”
mentioning
confidence: 99%
“…1 These cells originate from tumors and a subpopulation has been shown to be pre-cursors to metastasis. 2 In addition to this putative role, it is well known that these circulating tumor cells correlate with disease progression, 3 that they can be captured even in early disease, 4 and that they can be used to gauge functional cell responses to pharmaceuticals 5 or the genetic character of the cancer. 6 This information from captured CTCs is valuable to both clinicians and researchers particularly in the context of pancreatic cancer, in which the presence of circulating pancreatic cells precedes a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, circulating pancreatic cells exist in a subset of patients without cancer but with potentially cancerous pancreatic cystic lesions. 4 To obtain this information, CTCs have been successfully captured from blood samples through mechanical, 7 electromechanical 8 and immunoaffinity methods, 9-11 the last being the most common. However, challenges exist capturing subsets of CTCs that have reduced antigen expression, often associated with the epithelial to mesenchymal transition (EMT) 12 or acquired resistance to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…18 Separately, these obstacle arrays have been used to generate size-dependent collision dynamics, bringing target cells into contact with the antibodies on the obstacle surface, while displacing contaminating cells onto trajectories with infrequent cell-obstacle collisions; this technique has been termed geometrically enhanced differential immunocapture (GEDI). 6,11,27 This work focuses on combining differential DEP response in obstacle arrays with immunocapture, so as to capture target cells on the obstacle surfaces using antibody-antigen binding. Although the ideal DEP-obstacle array system would generate a uniformly high electric field around the obstacles, attracting cells experiencing pDEP to the obstacle capture surface, such a device would require electrodes on the side of each obstacle and would be difficult to fabricate using conventional techniques.…”
Section: Introductionmentioning
confidence: 99%